VALIDATION OF GEORGIAN VERSIONS OF BRIEF DEPRESSION AND ANXIETY QUESTIONNAIRES - Javakhishvili, Nino; Schwartz, Seth J.; Skhirtladze, Nino (Georgian Psychological Journal, 2022)
Background. This article presents the data validating Georgian versions of brief depression (CESD Boston Form) and anxiety (GAD7) measures. These two scales have been widely used in English with satisfactory validity and reliability and translated and used in many other languages, however, validation reports of GAD7 are relatively rare and the present study is the ﬁrst to validate the CESD Boston 10-item Form in a language other than English. Methods. Data were collected from a sample of 889 Georgian young adults, who, among others, ﬁlled out CESD Boston Form, GAD7, the Satisfaction with Life Scale and the Rosenberg Self-Esteem Scale. Results. Conﬁrmatory factor analysis of data indicated that one-factor solution provides a good ﬁt for both scales. A multi-group CFA supported at least partial conﬁgural, metric and scalar invariance across gender. Both scales provide scores with high internal consistency. Discriminant validity for the CESD Boston Form and the GAD7 was provided using their correlations with life satisfaction and self-esteem measures that had been previously validated with Georgian samples. Conclusions. The present study has provided Georgian versions of two brief measures of internalizing symptoms. These scales will help to satisfy the clinical assessment needs among Georgian mental health professionals and will serve as a model for other societies with similar needs.